Washakie Letters Of Willie Ottogary Northwestern Shoshone Journalist and Leader, 1908-1929 - Kreitzer, Matthew (Utah State University Press, 2000)
Writings by American Indians from the early twentieth century or earlier are rare. Willie Ottogary's letters have the distinction of being firsthand reports of an Indian community's ongoing social life by a community member and leader. The Northwestern Shoshone residing at the Washakie colony in northern Utah descended from survivors of the Bear River Massacre. Most had converted to the Mormon Church and remained in northern Utah rather than moving to a federal Indian reservation. For over twenty years, local newspapers in Utah and southern Idaho regularly published letters from Ottogary reporting happenings-personal milestones and health crises, comings and goings, social events, economic conditions and activities, efforts at political redress-at Washakie and other Shoshone communities in the intermountain West. Matthew Kreitzer compiled and edited the letters of Ottogary and added historical commentary and appendices, biographical data on individuals Ottogary mentioned, and eighty-five rare historical photographs.